CHANGES IN THE PHYSICOCHEMICAL PARAMETERS OF CHESTNUT SOILS IN WESTERN KAZAKHSTAN UNDER THE INFLUENCE OF THE GRAZING TECHNOLOGIES - B. Nasiyev, B. N.; Bekkaliyev, A.K.; Zhanatalapov, N.; Shibaikin, V.; Yeleshev, R. (Periodico Tche Quimica, 2020)
Managing pasture resources of Western Kazakhstan is complicated due to the deterioration of the physicochemical parameters of soils, manifesting degradation, and alkalinization as a result of intensive grazing. The research has been aimed at studying the technology of cattle grazing for preserving the physicochemical parameters of soils and increasing the efficiency of pasture use. The assessment and statistical analysis of physicochemical indicators of soils were carried out with standard methods during 2018 - 2019, which allowed identifying the most optimal grazing technology. The results of the research showed that under the influence of intensive grazing, physicochemical parameters worsened, a decrease in the humus reserves by 10.88-12.35% was detected, soil degraded to the third degree, and became alkaline as a result of the increase in exchangeable sodium to 1.65 cmol (equiv.)/kg. The technology of moderate cattle grazing favorably affects the physicochemical parameters of the soils of pasture ecosystems. The chestnut soils of the pastures, where moderate grazing technology was applied, remained resistant to degradation and salinization. With this technology, the soil humus was reliably preserved at the level of 1.15-2.50%, mobile phosphorus was within the optimal range of 0.87-1.60 mg/100g. It has been concluded that it is important to use the technology of moderate cattle grazing to improve the management of pasture resources, which is the scientific novelty of the research. Управление пастбищными ресурсами Западного Казахстана затруднено из-за ухудшения физико-химических параметров почв, проявления деградации и ощелачивания в результате интенсивного выпаса скота. Исследования были направлены на изучение технологии выпаса скота для сохранения физико-химических параметров почв и повышения эффективности использования пастбищ. Оценка и статистический анализ физико-химических показателей почв проводились стандартными методами в течение 2018-2019 годов, что позволило определить наиболее оптимальную технологию выпаса. Результаты исследований показали, что под воздействием интенсивного выпаса ухудшились физико-химические показатели, выявлено снижение запасов гумуса на 10,88-12,35%, почва деградировала до третьей степени и стала щелочной в результате увеличения обменных свойств. натрия до 1,65 смоль (экв.) / кг. Технология умеренного выпаса крупного рогатого скота благоприятно влияет на физико-химические показатели почв пастбищных экосистем. Каштановые почвы пастбищ, на которых применялась умеренная технология выпаса, оставались устойчивыми к деградации и засолению. При такой технологии гумус почвы надежно сохранялся на уровне 1,15-2,50%, подвижный фосфор находился в оптимальном диапазоне 0,87-1,60 мг / 100 г. Сделан вывод о важности использования технологии умеренного выпаса скота для улучшения управления пастбищными ресурсами, что является научной новизной исследования.
Keywords: импакт-фактор 2020; периодическое издание; научный журнал; зарубежное издание; зарубежные авторы; дальнее зарубежье; томсон; зко; процентиль 70; q2; параметры почвы; управление пастбищными ресурсами; умеренный выпас скота